A titanium dioxide nanoparticle sandwiched separator for Na–O2 batteries with suppressed dendrites and extended cycle life. Issue 32 (5th April 2018) - Yang, Hao; Sun, Jianchao; Wang, Hang; Liang, Jing; Li, Haixia
Abstract : A new TiO2 sandwiched separator is used in Na–O2 batteries, effectively inhibiting dendrites and extending their cycle life. Abstract : Na–O2 batteries are highly valued batteries with high energy density and low over-potentials, but limited by the threat of sodium dendrites. In this paper, a new trilayer separator with TiO2 nanoparticles as the middle layer is proposed, which can effectively inhibit the growth of sodium dendrites. The TiO2 sandwiched separator was used in a Na–O2 battery, and increased its cycle life. This work provides a new approach to extend the cycle life of sodium-based rechargeable batteries with a sandwiched separator.